The Relationship Between Self-Efficacy and Medication Adherence Among Hypertensive Patients in Langke Rembong, Manggarai - Iwa, Kornelia R; Eka, Angelina R; Wea, Lidwina Dewy; Krowa, Yuliana R R (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Hypertensive patients must adhere to their prescribed medications to maintain optimal health. Non-adherence to medication increases the risk of coronary heart disease, including congestive heart failure (CHF) and stroke. One of the key factors influencing consistent medication-taking behavior is self-efficacy. This study aims to examine the relationship between self-efficacy and medication adherence among hypertensive patients in the Langke Rembong sub-district of Manggarai District. This research involved 134 hypertensive patients from two community health centers in the Langke Rembong sub-district. Data were collected using a self-efficacy questionnaire and the Probabilistic Medication Adherence Scale (ProMAS). Descriptive statistics and the Spearman rank correlation test were used for data analysis. The findings revealed a significant relationship between self-efficacy and medication adherence (p-value = 0.000, r = 0.325**). Therefore, to improve medication adherence, it is essential to enhance self-efficacy by increasing patients' motivation and health awareness.